Opportunities and Challenges in Early-Stage TB Drug Discovery: Targeting DNA Replication as a Case Study - Prof Valerie Mizrahi; Melissa Chengalroyen; Sasha Lynch; Mandy Mason (International Journal of Infectious Diseases)
The TB drug pipeline has begun to deliver new and repurposed drugs and combinations which have revolutionized the treatment of drug-resistant TB and shown that treatment-shortening is an achievable goal. Maintaining this momentum requires replenishment of the pipeline with high-quality ‘hit’ compounds that show potent and selective inhibitory activity with mechanistic novelty against Mycobacterium tuberculosis (Mtb). This is a key objective of the TB Drug Accelerator (TBDA), a public-private-academic partnership focused on delivering new treatment-shortening drug regimens for TB. Of the vital cellular processes targeted by TB drugs in clinical use, DNA replication stands out as significantly under-exploited. In this talk I will illustrate how we have used biological profiling tools to identify and elucidate the mechanisms of action of novel antimycobacterial agents, including those that target the DNA replication machinery in mycobacteria, and to identify bacillary factors that mitigate the efficacy of these agents. These studies have laid a foundation for drug discovery efforts targeting the ‘core-clamp’ – the heart of the DNA replication machinery – in M. tuberculosis.